The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1126/scitranslmed.aaw8718
|View full text |Cite
|
Sign up to set email alerts
|

The human tissue-resident CCR5 + T cell compartment maintains protective and functional properties during inflammation

Abstract: CCR5 is thought to play a central role in orchestrating migration of cells in response to inflammation. CCR5 antagonists can reduce inflammatory disease processes, which has led to an increased interest in using CCR5 antagonists in a wide range of inflammation-driven diseases. Paradoxically, these antagonists appear to function without negatively affecting host immunity at barrier sites. We reasoned that the resolution to this paradox may lie in the CCR5+ T cell populations that permanently reside in tissues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 65 publications
2
57
0
1
Order By: Relevance
“…Only highly specialized laboratories are able to conduct experiments to investigate immune responses against HLA class-I and class-IIrestricted viral epitopes mediated by CD8+ and CD4+ T lymphocytes, respectively, to confirm the conjecture of a cellular (rather than humoral) immunity against SARS-CoV-2. Moreover, the T lymphocytes responsible for clinically relevant antiviral immune responses have high chances to be locally present in, or close to, respiratory epithelia but have comparatively low chances to be detectable in peripheral blood [57][58][59]. It is well possible that the exclusive detection of humoral immunity (antibodies against SARS-CoV-2) leads to an underestimation of the anti-SARS-CoV-2 immune responses.…”
Section: Roles Of Humoral and Cellular Immune Re-sponsesmentioning
confidence: 99%
“…Only highly specialized laboratories are able to conduct experiments to investigate immune responses against HLA class-I and class-IIrestricted viral epitopes mediated by CD8+ and CD4+ T lymphocytes, respectively, to confirm the conjecture of a cellular (rather than humoral) immunity against SARS-CoV-2. Moreover, the T lymphocytes responsible for clinically relevant antiviral immune responses have high chances to be locally present in, or close to, respiratory epithelia but have comparatively low chances to be detectable in peripheral blood [57][58][59]. It is well possible that the exclusive detection of humoral immunity (antibodies against SARS-CoV-2) leads to an underestimation of the anti-SARS-CoV-2 immune responses.…”
Section: Roles Of Humoral and Cellular Immune Re-sponsesmentioning
confidence: 99%
“…CCR5 is also expressed by tissue-resident memory T cells. These CCR5 + cells support barrier immunity (Davis et al, 2019).…”
Section: Introductionmentioning
confidence: 97%
“…Within the T cell compartment, a near 1:1 CD4/CD8 T cell ratio was observed in healthy endometrial biopsies at the secretory phase of the menstrual cycle [54][55][56]. This distribution substantially differs from that of blood (in which CD4 T cells are more frequent) and mirrors that of other barrier tissues that are largely populated by Trm cells, including the endocervix, ectocervix, and vagina [45,57,58]. Indeed, endometrial memory T cells (defined by CD45RO positivity) expressed CD69 (and to a lesser extent, CD8 T cells coexpressed CD103) [54] suggesting that Trm cells are present at the window of implantation.…”
Section: Tissue Residency: Preimplantationmentioning
confidence: 90%
“…While most Trm cells have a Tem-like phenotype, those with Temra phenotypes can also contribute to tissue residence [ 58 ], yet do not express CD45RO, potentially explaining the reported CD69 expression in CD45RO − endometrial T cells [ 54 ]. In line with bona fide tissue residence, CD69 + memory T cells isolated from the endometrium express the proteins PD-1 [ 54 ] or CCR5 [ 55 ] and transcripts for CD49a [ 59 ], mirroring phenotypic and transcriptional signatures broadly shared by human Trm cells across mucosal and lymphoid tissues [ 45 , 49 , 57 ]. While CCR5 expression has long been associated with a Th1 phenotype [ 60 ], a recent study demonstrated that CCR5 + CD4 T cells in healthy and inflamed human barrier tissue are actually potent IL-17 producers [ 45 ].…”
Section: The Memory T Cell Compartment Changes During the Course Omentioning
confidence: 99%
See 1 more Smart Citation